Metalaxyl resistance, mating type and pathogenicity of Phytophthora infestans in Uganda - Mukalazi, J.; Adipala, E.; Sengooba, T.; Hakiza, J.J.; Olanya, M.; Kidanemariam, H.M. (Crop Protection, 2001)
A total of 81 isolates of Phytophthora infestans (Mont.) de Bary were recovered from late blight infected samples collected from different areas of Uganda in 1998/1999. They were analyzed for their resistance to metalaxyl fungicide, mating types, and cross infection between potato and tomato hosts. Sensitivity to metalaxyl was determined by growing isolates on 10% V8 medium amended with 0, 5 and 100μg/ml metalaxyl. Overall 44.4% of the isolates tested were resistant to metalaxyl, 23.5% were intermediate and 31.2% were sensitive. Mating type was determined on 80 isolates using an A1 (1724) isolate and by growing the same isolates in pure culture (selfing). Fifty percent of the isolates produced oospores by matings and selfings, 22.5% by mating only and 10% by selfing only; 18% did not produce oospores in the two tests. Twenty seven of the P. infestans isolates from potato-infected tomato. The majority of these isolates were highly resistant to metalaxyl and produced oospores by either mating or selfing or both.
Keywords: Late blight; Metalaxyl resistance; Mating type